Harnessing Islamic Teachings for Climate Justice: Pathways for Faith-Based Environmental Action - Sadali (Sinergi International Journal of Islamic Studies, 2023)
This narrative review explores the contribution of Islamic teachings to environmental ethics and sustainability, aiming to assess how religious values influence environmental behavior, policy, and education in Muslim communities. Drawing on academic literature from databases such as Scopus, PubMed, and Google Scholar, the study synthesizes both conceptual and empirical findings related to Islamic environmental principles, particularly the concepts of khalifah, amanah, tawhid, and mizan. These principles are increasingly reflected in institutional practices by organizations such as Muhammadiyah, Nahdlatul Ulama, and Islamic Relief Worldwide. The study reveals that Islamic ethical frameworks are not only theoretically robust but also practically applied through community-based environmental programs, sustainable finance, and green education initiatives. However, systemic challenges such as fragmented policy support, limited environmental education, and weak integration between religious and public sectors hinder broader impact. The discussion highlights the role of Islamic education and national policies in strengthening environmental awareness and fostering a sense of spiritual responsibility toward nature. It also identifies opportunities for global collaboration through faith-based environmental strategies. The review concludes that aligning Islamic ethics with environmental governance can offer powerful, culturally relevant solutions to ecological crises, and recommends further interdisciplinary and cross-faith research to scale these efforts globally.